2014
DOI: 10.1371/journal.pone.0084455
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Subcellular Localization of Hopanoid Lipids in Bacteria Using NanoSIMS

Abstract: The organization of lipids within biological membranes is poorly understood. Some studies have suggested lipids group into microdomains within cells, but the evidence remains controversial due to non-native imaging techniques. A recently developed NanoSIMS technique indicated that sphingolipids group into microdomains within membranes of human fibroblast cells. We extended this NanoSIMS approach to study the localization of hopanoid lipids in bacterial cells by developing a stable isotope labeling method to di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 30 publications
1
27
0
Order By: Relevance
“…In the marine cyanobacterium Crocosphaera watsonii , hopanoids are present in insoluble, detergent-resistant membrane fractions, as is common for raft-forming lipids in eukaryotes 80 . Microanalysis of isotope-labelled hopanoids in the cyanobacterium Nostoc punctiforme and in R. palustris TIE-1 also showed that hopanoids preferentially localize to regions of high membrane curvature, where high degrees of membrane tension may require thicker, more condensed membranes 81 . Although these collective data are promising, further biophysical analyses of live membranes will be needed to determine whether hopanoids indeed form lipid rafts in bacterial cells.…”
Section: Biological Functions Of Hopanoidsmentioning
confidence: 93%
“…In the marine cyanobacterium Crocosphaera watsonii , hopanoids are present in insoluble, detergent-resistant membrane fractions, as is common for raft-forming lipids in eukaryotes 80 . Microanalysis of isotope-labelled hopanoids in the cyanobacterium Nostoc punctiforme and in R. palustris TIE-1 also showed that hopanoids preferentially localize to regions of high membrane curvature, where high degrees of membrane tension may require thicker, more condensed membranes 81 . Although these collective data are promising, further biophysical analyses of live membranes will be needed to determine whether hopanoids indeed form lipid rafts in bacterial cells.…”
Section: Biological Functions Of Hopanoidsmentioning
confidence: 93%
“…Since sterols are absent from most bacterial membranes, domain organization should depend on sterol surrogates and, hence, the involvement of polyisoprenoid lipids has been proposed (reviewed in [161]). A recent study using nanoSIMS has suggested hopanoid (pentacyclic triterpenoids structurally similar to steroids)-enriched domains in cyanobacterium Nostoc punctiforme [163]. …”
Section: Direct Evidence For Submicrometric Lipid Domains In Livinmentioning
confidence: 99%
“…Hopanoids are bacterial pentacyclic triterpenoids that are analogous to eukaryotic steroids structurally and biosynthetically (Ourisson et al, 1987; Doughty et al, 2011; Welander et al, 2012), but their cellular roles are poorly understood (Doughty et al, 2014). Hopanoids may play a role in the alteration of cell membrane permeability in adaptation to extreme environmental conditions in many bacteria.…”
Section: Discussionmentioning
confidence: 99%